EFFECT OF FINANCIAL LEVERAGE ON FIRM VALUE OF LISTED OIL AND GAS FIRMS IN NIGERIA - Agbachi, Vincent Onyeneke; Nwankwo, Bobby Godwin Ogbogu; Eneh, Catherine Amoge; Agu, Charles Ikechukwu (ESUT JOURNAL OF SOCIAL SCIENCES, 2026)
The study examined the effect of financial leverage on the firm value of listed oil and gas companies in Nigeria. The specific objective was to determine the effect of total debt to equity ratio, total debt to asset ratio and long-term debt to asset ratio on the net asset per share of listed and gas firms in Nigeria. The study deployed ex-post facto research design. The population is made of nine (9) oil and gas companies that are publicly listed on the Nigerian Exchange Group. The selection of firms for the sample size was based on purposive sampling. In this study, specifically, five (5) out of the available nine (9) firms were chosen. Secondary data were extracted from annual reports of oil and gas companies over a ten-year period, spanning from 2014 to 2023. The collected secondary data was coded into the into the statistical software REVIEWS Version 11. To test the hypotheses, Ordinary Least Square regression analysis was conducted at a 5% significance level. The findings showed that: total debt to equity ratio has a negative but non-significant effect on the net asset per share of listed oil and gas firms in Nigeria (β = -0.700522; p-value = 0.7772); total debt to asset ration has a positive and significant effect on the net asset per share of listed oil and gas firms in Nigeria (β = -82.91655; p-value = 0.0394); long term debt to asset ratio has a negative and significant effect on the net asset per share of listed oil and gas firms in Nigeria (β = -111.0643; p-value = 0.0050). In conclusion, firms with substantial long-term debt may see a reduction in their net asset per share, reflecting the adverse effects of prolonged financial obligations. In light of the negative effect of long-term debt to asset ratio on net asset per share, the board of directors should implement policies to limit excessive long term borrowing. They should prioritize financial strategies that maintain a balanced approach to long-term debt, ensuring that it does not compromise the firm’s financial flexibility or lead to value erosion.